Study of Climatic Pattern and Water Resources from Citizen Science’s Perspective in Namobuddha Municipality, Kavre, Nepal - Thapa, Jamuna; Gautam, Narayan Prasad; Thapa, Khadga Bahadur (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
This study has been initiated to carry out the research on climatic patterns along with water resources from local communities’ perspectives in Namobuddha Municipality, Kavre, Nepal. The study area is located in the eastern part of Kathmandu which is about 35 km away from it. This study has focused on investigating climatic patterns and water resources available in the study area. It was especially carried out utilizing citizens’ perspectives. Mixed qualitative and quantitative methods were used in this study. Total 66 questionnaire surveys and two key informant interviews were conducted in the Simalchaur Sympati area of Namobuddha Municipality which has about 600 households. Required Meteorological data were taken from the Department of Hydrology and Meteorology, Nepal. Results from this study showed that the average, minimum and maximum temperatures were in the increasing trend. However, the average annual along with the monsoon rainfalls were in the decreasing trend. The inhabitants have experienced warmer summer and winter, scarcity of water for domestic as well as for agriculture purposes. Local communities also deplored less ground water flow in their springs. This study has clearly signified the drying up of surface and ground water resources. In overall context, this study output was similar to the global pattern as temperatures are in increasing trend whereas precipitation is in decreasing trend. It signified the need for effective adaptation strategies to combat against the adverse impacts of changing climatic patterns especially for the management of water resources in the study area.